2004
DOI: 10.1111/j.1365-2575.2004.00162.x
|View full text |Cite
|
Sign up to set email alerts
|

Principles of canonical action research

Abstract: Despite the growing prominence of canonical action research (CAR) in the information systems discipline, a paucity of methodological guidance continues to hamper those conducting and evaluating such studies. This article elicits a set of five principles and associated criteria to help assure both the rigor and the relevance of CAR in information systems. The first principle relates to the development of an agreement that facilitates collaboration between the action researcher and the client. The second princip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
502
0
18

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 558 publications
(558 citation statements)
references
References 55 publications
4
502
0
18
Order By: Relevance
“…Third, action research (Baskerville & Wood-Harper, 2002;Davison, Martinsons, & Kock, 2004) provides a relevant methodology for projects that meet the objectives of both research and practice. Engaged scholarship (Mathiassen & Nielsen, 2008;Van de Ven, 2004) provides a similar tradition.…”
Section: Barrier: Research Methodsmentioning
confidence: 99%
“…Third, action research (Baskerville & Wood-Harper, 2002;Davison, Martinsons, & Kock, 2004) provides a relevant methodology for projects that meet the objectives of both research and practice. Engaged scholarship (Mathiassen & Nielsen, 2008;Van de Ven, 2004) provides a similar tradition.…”
Section: Barrier: Research Methodsmentioning
confidence: 99%
“…Particular threats are that second author's involvement in the release planning affects researcher bias and that already the awareness of being observed affects the behavior of practitioners [30]. The former threat was a conscious decision to increase the accuracy and completeness of the description as practiced in action research [31]. Researcher bias was controlled by triangulating data sources.…”
Section: Threats To Validitymentioning
confidence: 99%
“…Due to the cooperative nature of this research project, the research method adopted for both companies was the participative research method, action research [4]. In order to properly describe and differentiate the research methods used, we describe them according to the five principles suggested by Davison et al [9] (table 1) and the three aspects of control structures suggested by Avison et al [3] (table 2). At the Alpha company, the research on how to use project workshops to define software process was carried out during 2003.…”
Section: Methodsmentioning
confidence: 99%